Muskox and Man in the Subarctic: An Archaeological View - Gordon, Bryan C. (ARCTIC, 1977)
Archaeologist Bryan C. Gordon, National Museum of Man, Ottawa, comments on the recent paper by Ernest S. Burch, Jr. in Arctic. He puts forward possible reasons for the relative absence of muskox remains. He concludes that, while barrenland archaeologists rightfully regard the caribou as the staff of life to the prehistoric indigenes, they do not disregard the muskox, but merely seek to accord it a correct relative importance.